2019
DOI: 10.4321/s1575-06202019000300004
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, positive affectivity and wellbeing in prison: a comparative study between young and older prisoners

Abstract: Objective: To explore socio-demographic, psychological and psychopathological characteristics, as well as to evaluate behaviour in a sample of inmates. Material and methods: A sample of 182 young and elderly inmates of the Madrid III Prison was used. The research was carried out with a battery of self-report psychological questionnaires and objective measurements obtained through the prison files. Comparisons of means were made to see if there are significant differences between the two groups (young and elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
(37 reference statements)
0
4
0
1
Order By: Relevance
“…The predominant mental health contributory factors identified related to poor coping skills and difficulties managing emotions. A focus on education, developing emotional skills and building resilience among the prison population may lead to improvements in general mental health and wellbeing, engagement with services, improved relationships and progress in their sentence management plan (Chiclana et al , 2019). Substance abuse was also a primary contributory factor associated with self-harm among the prison population in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant mental health contributory factors identified related to poor coping skills and difficulties managing emotions. A focus on education, developing emotional skills and building resilience among the prison population may lead to improvements in general mental health and wellbeing, engagement with services, improved relationships and progress in their sentence management plan (Chiclana et al , 2019). Substance abuse was also a primary contributory factor associated with self-harm among the prison population in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…Individualised approaches need to be taken to identify the interests, feelings and experiences of elderly inmates, who are generally less demanding and less inclined to voice their dissatisfactions than younger inmates. This may be due to the fact that elderly inmates present greater psychological adjustment, more internal resources and better adaptation to the prison setting in comparison to young prisoners, independently of the time spent in prison 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The research indicates that among detainees, stress-related diseases are diagnosed more often than in the general population (Bronson and Berzofsky, 2017; Clarke and Waring, 2012; Houle, 2014; Massoglia and Pridemore, 2015; Howell et al , 2016). Analysis of the available literature has shown that research dealing with the issue of stress and emotions among detainees are carried out with the use of various, often non-standardised or original research tools, which makes reliable comparison of results difficult (Unver et al , 2013; Reta et al , 2020; Chiclana et al , 2019; Constantino et al , 2016; Baidawi, 2016; Rose et al , 2020; van den Berg et al , 2016; Ahmad and Mazlan, 2014; Malik et al , 2019; Joon Jang, 2020). This provided the motivation to explore the above issue using standardised and reliable research tools.…”
Section: Discussionmentioning
confidence: 99%